66.9k views
13 votes
Solve for x 3(6 - x) + 2x = 15
HELP PLEASE I GET SO CONFUSED​

2 Answers

6 votes

Answer:

x=3

Explanation:

PEMDAS

Or parenthesis, exponent, multiply, divide, addition, and subtraction. (Order of operations)

3(6-x) + 2x = 15

Start with multiplying

18 - 3x + 2x = 15

then combine like terms

18 - x = 15

subtract 18 from each side

-x = -3

times each side by -1 to remove the negative

x = 3

User SomePerson
by
4.7k points
5 votes

3(6 - x) + 2x = 15

18 - 3

-3x+2x = 15

18 - x = 15

-x = 15 - 18

-x =- 3

x = 3

easy - peasy

User Forethinker
by
4.8k points